The Role of Bhabinkamtibmas in the Implementation of the Kampung Siaga Candi Hebat Program in Polaman Village, Mijen Sub-district to Realize Conducive Community Security and Order - Aerlangga Yoga Prasetyo (Indonesian Journal of Police Studies, 2021)
This research is motivated by the increasing problems of the Covid-19 virus pandemic, especially the jurisdiction of the Semarang Polrestabes. The central government has also tightened community activities. Based on the order of the National Police Chief through a telegram regarding the establishment of the "Kampung Tangguh Nusantara", the Semarang Police Station established the Great Temple Alert Village program. In this case, the researchers focused on conducting research in the Polaman Village of the Mijen Police Sector on the grounds that the ability of Bhabinkamtibmas in implementing the program was considered more successful than other villages in the Mijen Polsek area. The purpose of this research is to find out the role of Bhabinkamtibmas in implementing the Kampung Siaga Candi Hebat program which can reduce the crime rate and suppress the spread of Covid-19 in the Polaman Village, Polsek Mjen. As a knife of analysis is the Bhabinkamtibmas Concept, Management Theory, SWOT Analysis Theory. This research was conducted with a qualitative approach and used descriptive analysis and data collection by interview, observation, and document review. Research located in the jurisdiction of the Mijen Police. The results of the research show that the implementation of the Kampung Siaga Candi Hebat Program can reduce the crime rate and the spread of Covid 19 in the Polaman sub-district of the Mijen Polsek, even specifically the reduction of Covid 19 is considered successful compared to other police jurisdictions in the Semarang Polrestabes line. The author also found several obstacles, especially the public's lack of understanding of the program, but slowly Bhabinkamtibmas has succeeded in providing a good understanding so that this program can run smoothly. In conclusion, that the program has succeeded through the maximum role of Bhabinkamtibmas and the authors suggest that the leadership should give an award to Bhabinkamtibmas, Polaman Village, Mijen Police, so that Bhabinkamtibmas participate in the Binmas Dikjur, so that the costs of the program are fully borne by the Police.